2022
DOI: 10.1186/s12913-022-07466-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a standardised perioperative nutrition care pathway in upper gastrointestinal cancer surgery: a mixed-methods analysis of implementation using the Consolidated Framework for Implementation Research

Abstract: Background Implementation studies of complex interventions such as nutrition care pathways are important to health services research, as they support translation of research into practice. There is limited research regarding implementation of a nutrition care pathway in an upper gastrointestinal (UGI) cancer population. The aim of this study was to comprehensively evaluate the implementation process of a perioperative nutrition care pathway in UGI cancer surgery using The Consolidated Framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Although feasibility of recruitment of participants within the study context was described, description and analysis of the implementation process using implementation science can assist in interpretation of the outcomes of the study, and in translating this research into future practice 27,30 . A complex analysis of implementation using the Consolidated Framework for Implementation Research (CFIR) has also been undertaken, 31 which has been reported in an additional manuscript 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although feasibility of recruitment of participants within the study context was described, description and analysis of the implementation process using implementation science can assist in interpretation of the outcomes of the study, and in translating this research into future practice 27,30 . A complex analysis of implementation using the Consolidated Framework for Implementation Research (CFIR) has also been undertaken, 31 which has been reported in an additional manuscript 32 …”
Section: Discussionmentioning
confidence: 99%
“…27,30 A complex analysis of implementation using the Consolidated Framework for Implementation Research (CFIR) has also been undertaken, 31 which has been reported in an additional manuscript. 32…”
Section: Discussionmentioning
confidence: 99%